3D shape optimization of fan vanes for multiple operating regimes subject to efficiency and noise-related excellence criteria and constraints - Marinić-Kragić, Ivo; Vučina, Damir; Milas, Zoran (Engineering applications of computational fluid mechanics, 2016)
Fully generic 3D shapes of centrifugal roof fan vanes are explored based on a custom-developed numerical workflow with the ability to vary the vane 3D shape by manipulating the control points of parametric surfaces and change the number of vanes and rotation speed. An excellence formulation is based on design flow efficiency, multi-regime operational conditions and noise criteria for various cases, including multi-objective optimization. Multiple cases of optimization demonstrate the suitability of customized and individualized fan designs for specific working environments according to the selected excellence criteria. Noise analysis is considered as an additional decision-making tool for cases where multiple solutions of equal efficiency are generated and as an additional criteria for multi-objective optimization. The 3D vane shape enables further gains in efficiency compared to 2D shape optimization, while multi-objective optimization with noise as an additional criterion shows potential to greatly reduce the roof fan noise with only small losses in efficiency. The developed workflow which comprises (i) a 3D parametric shape modeler, (ii) an evolutionary optimizer and (iii) a computational fluid dynamics (CFD) simulator can be viewed as an integral tool for optimizing the designs of roof fans under custom conditions.